Facile microwave synthesis, structural, optical, and magnetic properties of Zn2+ doped CoAl2O4 spinel nanoparticles. Issue 3 (4th March 2023) - Dash, Chandra Sekhar; Rajabathar, Jothi ramalingam; Al-Lohedan, Hamad; Arokiyaraj, Selvaraj; Ramachandran, S.; Sukumar, M.; Revathi, R.; Anitha, G.; Sundararajan, M.
Abstract: CoAl2 O4 and Zn:CoAl2 O4 nanoparticles (NPs) were synthesized via microwave combustion process (MCP) and L-alanine used as fuel. The average crystallite size is found in the range of 10–18 nm. Spherical aggregated particle morphology is obtained for synthesized sample and the same confirmed by HR-SEM images and nonexistence of impurities in the prepared samples were confirmed by EDX spectra. The band gap values of the prepared samples were found to be in the range of 3.35–2.32 eV. Further in FTIR spectra a couple of strong absorption bands observed which lie in the range of 500–1100 cm −1, ensuring the formation of cubic spinel structure. Thermal studies confirmed the weight loss and exothermic transitions in pure and Zn 2+ ion doped cobalt aluminate samples. The prepared Zn ion modified cobalt aluminate samples exhibited diamagnetic magnetic characteristics at room temperature and the same have been confirmed. Graphical Abstract: UF0001 The prepared Zinc ion modified cobalt aluminate spinel structure samples exhibited diamagnetic magnetic characteristics at room temperature and the same have been confirmed by the Magnetization–Field (M − H) hysteresis curves. The obtained images confirm the facile formation of crystallized grains comprising of pores and agglomerated coalescence morphology. Additionally, tiny secluded grains with pores and pore-walls ensuing from fused grains with discrete grain boundaries are noticed.